(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes the views of the foreign scientists on the creativeness of a teacher and student as the notions of the creativeness – creating the novelty, creative capability in problem solutions, uniqueness in their contents, practicality, extraordinariness and freedom.